Ethics of Communication in Islam: Driving Success in Sharia Cooperative Marketing - Syaripudin, Syaripudin; Fahrurrozi, Fahrurrozi; Fakhri, Mohammad (STKIP Singkawang, 2024)
Islamic communication ethics in the digital era significantly influence economic practices such as the development of Sharia cooperatives, where challenges like the lack of Sharia financial literacy and negative perceptions of Sharia Financial Institutions require an effective and ethical communication strategy. Therefore, this research aims to examine the role of Islamic communication ethics in strengthening persuasion among potential members of Sharia cooperatives in East Lombok. The research method used was descriptive qualitative, with a sample of five cooperatives selected through purposive sampling. Primary data were obtained from interviews and documentation, while data analysis was conducted through data reduction, presentation, and verification. The findings revealed that Islamic communication ethics, through principles such as Qaulan Ma’rufa, Qaulan Layyin, Qaulan Baligha, Qaulan Sadida, and Qaulan Karima, play a key role in strengthening trust and understanding between field workers and potential members of Sharia cooperatives in East Lombok, facilitating effective communication and increasing success in member recruitment. This approach integrates social, cultural, and religious aspects, significantly affecting the effectiveness of recruitment and building the integrity and reputation of the Sharia cooperative. In conclusion, Islamic communication ethics play a vital role in promoting the sustainable growth of Sharia cooperatives in East Lombok by integrating Islamic values into the communication process, which strengthens trust and facilitates a better understanding of Sharia financial products and services.